Vapor-liquid equilibria of CFC alternative refrigerant mixtures: Trifluoromethane (HFC-23) plus difluoromethane (HFC-32), trifluoromethane (HFC-23) plus pentafluoroethane (HFC-125), and pentafluoroethane (HFC-125) plus 1,1-difluoroethane (HFC-152a) - Lim, JS; Park, JY; Lee, BG (KLUWER ACADEMIC/PLENUM PUBL, 2000)
Isothermal vapor-liquid equilibria for three binary mixtures of CFC alternative refrigerants were determined ill an equilibrium apparatus in which both phases were continuously recirculated, The pressures and vapor and liquid compositions were measured for the binary systems trifluoromethane (HFC-23)+difluoromethane (HFC-32) and trifluoromethane (HFC-23)+pentafluoroethane (HFC-125) at 283.15 and 293.15 K and pentafluoroethane (HFC-125); 1,1-difluoroethane (HFC-152a) at 293.15 K. The experimental data were correlated with the Peng-Robinson-Stryjek-Vera equation of state using the Huron-Vidal original mixing rule. Calculated results with this equation showed good agreement with the experimental data.
Keywords: STATE